Juegos didácticos como herramienta pedagógica para la enseñanza del inglés en estudiantes de tercer año de básica en la escuela "Modesto Peñaherrera" Cotacachi Imbabura - Silva, Isabel M. (2022)
This Project is focused on the paradigm of constructivism within the virtual modality of teaching where it is intended to evaluate the application on online tool to promote the learning of the second language English to awaken in interest and motivation by creating a communication that encourages them to speak, sing and perform rhymes and participates between partners and teachers, This learning through interactive games is a good opportunity for students to compete and the winner can be stimulate and flatter the looser in the same way, since it is made known how much influence the use of didactic games can have to be used as tool in the learning of the second language. For this the project will be carried out in the Modesto Peñaherrera school in the Cotacachi canton with a sample of thirty-two students of the third year of basic education. Where what has been learned will be evaluated daily the use of interactive games and videos. At the end of the online learning will be evaluated qualitatively and quantitatively, small evaluation of multiple selection will be taken to known the degree of learning achieved by the students. Though the platform we will realized where it has the highest degree of dificulty in order to be able to reinforce the knowlege acquired where they can develop with the better language skills such as the listening,writing , reading and speaking.